2018
DOI: 10.1124/dmd.118.081612
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol and Calcipotriol Modulate Transport Activity of ABC Transporters and Exhibit Selective Cytotoxicity in MRP1-overexpressing Cells

Abstract: Efflux transporters P-glycoprotein (P-gp/ABCB1), multidrug resistance protein 1 (MRP1/ABCC1), and breast cancer resistance protein (BCRP/ABCG2) can affect the efficacy and toxicity of a wide variety of drugs and are implicated in multidrug resistance (MDR). Eight test compounds, recently identified from an intramolecular FRET-based high throughput screening, were characterized for their interaction with MRP1. We report that the active metabolite of vitamin D, calcitriol, and its analog calcipotriol are selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…Therefore, MRP1 can significantly reduce the efficacy of many different types of drugs and therapeutic agents. As MRP1 is known to have moderate to high expression in lung, breast and prostate tissues and plays an important role in tissue defence [42], we investigated the interaction of AuNCs (Au25(Capt)18) with this efflux transporter protein. MRP1 transport activity was evaluated by detecting the accumulation of the fluorescent anticancer drug, doxorubicin and a well-known substrate of MRP1.…”
Section: Pharmacokineticmentioning
confidence: 99%
“…Therefore, MRP1 can significantly reduce the efficacy of many different types of drugs and therapeutic agents. As MRP1 is known to have moderate to high expression in lung, breast and prostate tissues and plays an important role in tissue defence [42], we investigated the interaction of AuNCs (Au25(Capt)18) with this efflux transporter protein. MRP1 transport activity was evaluated by detecting the accumulation of the fluorescent anticancer drug, doxorubicin and a well-known substrate of MRP1.…”
Section: Pharmacokineticmentioning
confidence: 99%
“…Many conventional cytotoxic anticancer drugs (e.g., doxorubicin, vincristine and methotrexate) are substrates of ABC drug transporters, which led to a perception that the new targeted therapy drugs which are not very toxic may not be recognized and pumped out by ABC drug transporters. However, recent studies have shown that ABC drug transporters like P-gp and MRP1 can recognize a remarkable variety of these newer targeted therapy drugs and can reduce their efficacy as well [13,19,21,22]. Therefore, ABC drug transporters are considered very important therapeutic targets for the improvement of cancer chemotherapy and to overcome the MDR.…”
Section: Discussionmentioning
confidence: 99%
“…An important player involved in the failure of treatment in cancer is the resistance against chemotherapy known as multidrug resistance (MDR). It is a phenomenon that has been receiving great attention in the last 50 years [6,7] due to the sheer amount of mechanisms discovered and involved in the process of resistance which hinders the effectiveness of many anti-cancer drugs [8][9][10][11][12][13]. It is a challenge that needs to be further investigated and overcome and is a paramount factor in cancer recurrence and low survival rates [14][15][16][17]…”
Section: Cancer Todaymentioning
confidence: 99%
“…The resistant sublines HT29/DX and A549/DX were obtained by culturing cells in a medium containing increasing concentrations of doxorubicin. Every 5 passages, the concentration of doxorubicin was increased according to this protocol: 100 pM (passages 1-5), 250 pM (passages 6-10), 500 pM (passages 11-15), 1 nM (passages 16-20), 25 nM (passages 21-25), 50 nM (passages 26-30), and 100 nM (passages [31][32][33][34][35]. HT29/DX cells were used between passages 32 and 35, and were maintained in a medium with 100 nM doxorubicin, added three times/week, 6 h after cell seeding.…”
Section: Cancer Cell Linesmentioning
confidence: 99%
“…Nevertheless, very few of the studies focused on CS in MRP1-expressing cells compared with the experimental works focused on CS in P-gp-expressing cells [16,[28][29][30]. Due to the impact of MRP1 overexpression in cancer development and drug resistance, and the increasing evidence of its role in CS [19,22,31,32], the aim of the study is the identification of new CS-promoting agents having as the target the MDR protein MRP1. With this in mind, we had to identify proper MRP1 inhibitors, first.…”
Section: Introductionmentioning
confidence: 99%